Case Report: Successful application of endoscopic biliary accessories in a patient with complete esophageal stricture - Yan, Junjun; Liao, Qiangming; Ding, Bin (Frontiers in Medicine, 2025)
The endoscopic treatment of complete esophageal stricture presents a huge challenge. In instances where the esophageal lumen is nearly obliterated, preventing the passage of a dilating guide wire, conventional endoscopic bougie dilation is often difficult to perform. We report a case of patients with nearly complete esophageal stricture due to esophageal cancer surgery, leading to severe dysphagia and weight loss. Our strategy began with the achievement of anterograde esophageal access, facilitated by a biliary intubation method and aided by a 0.35-inch guidewire. Subsequently, we sequentially applied biliary dilators and balloon dilators, progressing along the guidewire to incrementally dilate the esophageal lumen up to the site of complete stenosis. The stenosis was successfully penetrated and dilated, and eventually the patient’s dysphagia was completely relieved. This case underscores the efficacy of the novel endoscopic treatment for biliary appendices in patients with refractory esophageal anastomotic stricture, offering a new therapeutic approach for clinical management.